CONSIDERING STRATEGIC FORMULATION FOR TAX REVENUE ENHANCEMENT IN DIRECTORATE GENERAL OF TAXES - Irwan Aribowo Aribowo; Agus Suryono; Khairul Muluk; Andy Fefta Wijaya (Politeknik Keuangan Negara STAN, 2023)
The Directorate General of Taxes (DGT) as a large organization certainly has directions and goals to be achieved. The main objective of the DGT is to achieve the tax revenue target. This main objective is set by the DGT to support the national development priority agenda. To achieve the main objective of DGT, a strategic formulation was considered out. This study aims to consider the importance of strategic formulations for DGT to increase tax revenue. This research is based on qualitative methods and descriptive analysis based on the actualization of strategic planning at DGT. The results of the study indicate that the strategic formulation is important for DGT to increase tax revenue, by: a). considering environmental realities, available resources and capacities; b) setting overall strategic objectives; c). identify the organization's mandate, clarify the vision, mission and values of the organization; d). assessing the external and internal environment; e) identify problems facing the organization, formulate and select strategies; and f) reassessing the strategy and strategic planning process.